Application of the Business Judgment Rule to State-Owned Enterprises: A Comparative Study Across Countries - Bagus Satrio Utomo (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The business judgment rule (BJR) is a legal principle that protects corporate directors and officers from liability for decisions made in their official capacity, provided they acted in good faith, with due care, and in the best interests of the company. While the BJR is well established in the context of private corporations, its application to state-owned enterprises (SOEs) raises complex issues due to their unique ownership structures, governance frameworks, and public accountability requirements. This article conducts a thorough comparative analysis of the application of the BJR to SOEs across different jurisdictions, examining the legal principles, judicial precedents, and regulatory regimes that shape the scope and contours of the BJR in the SOE context. The article identifies common themes and divergences in the approach of courts and policymakers to this issue, and evaluates the tensions between entrepreneurial discretion and public oversight that arise when applying the BJR to SOEs. Based on this analysis, the article proposes a framework for optimizing the BJR regime for SOEs, including recommendations for statutory reforms, superior governance methods, and judicial standards that can help balance the competing interests at stake. The article aims to provide valuable insights and guidance for policymakers, regulators, courts and SOE leaders grappling with the challenges of applying the BJR in different legal and institutional contexts worldwide.